Salidroside Improves Chronic Stress Induced Depressive Symptoms Through Microglial Activation Suppression - Fan, Yang; Bi, Yajuan; Chen, Haixia (Frontiers in Pharmacology, 2021)
Depression is a severe neurological disorder highly associated with chronic mental stress stimulation, which involves chronic inflammation and microglial activation in the central nervous system (CNS). Salidroside (SLDS) has been reported to exhibit anti-neuroinflammatory and protective properties on neurological diseases. However, the mechanism underlying the effect of SLDS on depressive symptoms has not been well elaborated. In the present study, the effects of SLDS on depressive behaviors and microglia activation in mice CNS were investigated. Behavioral tests, including Forced swimming test (FST), Open field test (OFT) and Morris water maze (MWM) revealed that SLDS treatment attenuated the depressive behaviors in stress mice. SLDS treatment significantly reduced the microglial immunoreactivity for both Iba-1 and CD68, characteristic of deleterious M1 phenotype in hippocampus of stress mice. Additionally, SLDS inhibited microglial activation involving the suppression of ERK1/2, P38 MAPK and p65 NF-κB activation and thus reduced the expression and release of neuroinflammatory cytokines in stress mice as well as in lipopolysaccharide (LPS)-induced primary microglia. Also, SLDS changed microglial morphology, attachment and reduced the phagocytic ability in LPS-induced primary microglia. The results demonstrated that SLDS treatment could improve the depressive symptoms caused by unpredictable chronic stress, indicating a potential therapeutic application of SLDS in depression treatment by interfering microglia-mediated neuroinflammation.